Pull-out behaviour of adhesives bonded structural connector - Zakaria, Mohamad Muzammil (2018)
Connections for timber structures using concealed bonded-in rods offer one possible solution to the development of more efficient joining methods. However the importance of certain basic joint characteristics, and the influence of adhesive type and properties, are not yet fully understood and as such design criteria are lacking. This paper describes a comprehensive experimental and numerical investigation into the fundamental material and joint geometry characteristics of rods bonded in to timber. The adhesive type and performance are both considered, along with test configuration and joint parameters that included rod and timber species. It was found that epoxy adhesives out-performed all other types investigated, and pull-out strengths can be significantly improved through careful selection and optimization of the joint geometry. Balau sample exhibited higher pull-out strength with a means of 10.43 MPa (τta) and 15.65 MPa (τra). This indicates that the shear strength values of the tested specimens were affected by the density of wood species although the results indicate a declining value of average shear strength due to the adhesive type. There is a strong correlation between the density of the wood and mean shear strength. Failure mode in softwood and hardwood is mostly related to the anatomical properties of the wood which influences the wettability of adhesive that has been use.